Blood loss, complications, and the role of suction drains in shoulder arthroplasty: a systematic review and meta-analysis - Luiz Henrique Oliveira Almeida, MD; Vitor La Banca, MD; Octavio Matsumoto, MD; Arthur Steven de Sá, MD; Ana Victória Palagi Viganó, MD; Gabriel Kalman, MedStud; Felipe Fernandes Gonzalez, MD, MSc; Guilherme Henrique Vieira Lima, MD; Joel Murachovsky, MD, PhD; Roberto Yukio Ikemoto, MD, PhD (JSES International)
Background: Total shoulder replacement, including both anatomic and reverse procedures are one of the treatment options for shoulder arthritis and proximal humerus fractures, with consistently favorable outcomes in terms of pain relief and function improvement. During surgery, some surgeons prefer to place suction drains in the deep tissue to prevent hematomas or seromas, thereby reducing risks like wound dehiscence and infections. However, the routine use of suction drains in other orthopedic surgeries, such as hip and knee arthroplasty, has been questioned, with studies suggesting they may lead to extended hospital stays and increased need for transfusions without significantly reducing complications. Given the conflicting evidence in the literature about suction drains in shoulder arthroplasty, this study aims to evaluate their efficacy in reducing complications and in consequence the need for hospital stay and reoperations. Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. The inclusion criteria encompassed studies comparing outcomes of patients undergoing shoulder arthroplasty (anatomic or reverse) with and without suction drains. Databases such as PubMed, Lilacs, Cochrane Library, and Scopus were searched, with no restrictions on language or publication date. Data extraction was performed for duration of hospital stay, transfusions, infections, wound dehiscence, reoperations, and hemoglobin changes. Meta-analyses were conducted using a random-effects model for mean differences (MDs) and odds ratios (ORs). Results: Six studies with a total of 22,710 patients were included. The mean patient age was 68.8 years, with a slight female predominance. Anatomic and reverse shoulder arthroplasties were both commonly performed. There was no significant difference in hospital stay (MD: 8.78 hours), infection rates (OR: 0.64; 95% confidence intervals (CI): 0.30-1.35), or reoperation rates (OR: 1.62; 95% CI: 0.16-16.23) between patients with drains and those without. However, hemoglobin loss was significantly greater in the drain group (MD: 0.31; 95% CI: 0.02-0.60). Conclusion: The use of suction drains in shoulder arthroplasty does not significantly reduce infection or wound-related complications and is associated with increased hemoglobin loss. These findings suggest that the routine use of drains in shoulder arthroplasty may not provide tangible benefits and should be reconsidered to optimize patient outcomes.